Pemberdayaan Ibu Rumah Tangga Melalui Kelompok Menjahit Deta dan Batik Kajang Padati di Kota Padang - Nofiandi, Tedi; Isnaini, Isnaini; Rahmadani, Sri (Jurnal Multidisiplin Teknologi dan Arsitektur, 2024)
This research is motivated by the empowerment of sewing training for housewives conducted by the Padang City DPRD in the last 2 years, the sewing training empowerment is one of the main points of thought of members of the Padang City Regional House of Representatives, but the training runs for 1 week and then is continued by the Deta sewing group voluntarily. However, over time the trainees have earned income from opening a business at home. The Actors involved make it interesting to research. The purpose of this study was to describe the strategy of empowering housewives through the Deta Sewing and Batik Kajang Padati groups in Padang City. This research uses a qualitative approach with a descriptive type, and the informant of this research is done by taking informants through purposive sampling technique, namely by looking for informants who match the criteria set by the researcher. The data collection method starts from the in-depth interview stage, observation and document data collection. The unit of analysis in this study is in the group, namely the deta sewing group and sewing empowerment participants in Padang City. Data analysis is carried out from several stages, namely data collection, data reduction, data presentation and conclusion drawing called the Miles and Hubermen model. The results of this study show that the sewing empowerment program in Padang City shows a positive impact in improving the skills and economy of housewives. Support, opportunities, and clear responsibilities, as well as the application of the ACTORS theory, are critical to the success of the program. The strategies used in the sewing empowerment program involve needs identification, training planning and implementation, collaboration with institutions, and ongoing support and evaluation to improve the skills, economic well-being, and social contribution of housewives.